Pemanfaatan Dan Pelatihan Penggunaan Marketplace Shopee Sebagai Sarana Pemasaran Pada Toko Maysara Hijab - Hamdani, Rita; Fadillah Rezky, Syarifah; Suherdi, Devri; Sari, Kartika; Syahputri, Astri (Cattleya Darmaya Fortuna, 2023)
The Maysara Hijab shop is one of the businesses located in Binjai City, precisely on Jl. Tuanku Imam Bonjol. The Maysara Hijab shop does not only sell hijabs, but also clothes for women. In the sales process, the owner of the Maysara Hijab shop only sells offline, namely waiting for customers to come to the store. So there is no container used to promote online. This is because the owner does not know how to carry out promotions and create a marketplace for promotional containers in selling their products. With these problems, we, as the PKM team, assisted in creating a marketplace at Shopee and assisted in promotion on social media. This partnership activity starts with registering to create an account for shop owners at Shopee, then creating a shop and entering product data and registering a free shipping shop. When the Maysara Hijab Shop was finished, the PKM Team assisted in training on using the Shopee Marketplace from entering new products, accepting orders and shipping products and disbursing funds from product sales. As a result of this PKM activity, it is hoped that the owner can independently manage his marketplace and be able to use the marketplace